2017
DOI: 10.1186/s12913-017-2305-1
|View full text |Cite
|
Sign up to set email alerts
|

Current status, challenges and the way forward for clinical pharmacy service in Ethiopian public hospitals

Abstract: BackgroundClinical pharmacy service has evolved steadily over the past few decades and is now contributing to the ‘patient care journey’ at all stages. It is improving the safety and effectiveness of medicines and has made a significant contribution to the avoidance of medication errors. In Ethiopia, clinical pharmacy service is in its initial phase, being started in July 2013. This study therefore aimed at assessing the status, challenges and way forward of clinical pharmacy service in the country.MethodsA cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…is study also reflected a shortage of pharmacy workforce and staff turnover, absence of a follow-up from responsible bodies, and a lack of enough salaries and incentives for health care providers as the challenges for the clinical pharmacy services in MTUTH. Similar findings were also reported in earlier studies conducted in Ethiopia [5,24] and elsewhere in Asia [13]. Hence, the hospital leadership should look into the possibilities of recruiting more health care providers and training of more professionals to render…”
Section: Discussionsupporting
confidence: 87%
“…is study also reflected a shortage of pharmacy workforce and staff turnover, absence of a follow-up from responsible bodies, and a lack of enough salaries and incentives for health care providers as the challenges for the clinical pharmacy services in MTUTH. Similar findings were also reported in earlier studies conducted in Ethiopia [5,24] and elsewhere in Asia [13]. Hence, the hospital leadership should look into the possibilities of recruiting more health care providers and training of more professionals to render…”
Section: Discussionsupporting
confidence: 87%
“…These studies are based on pharmacists’ reports from a variety of developing countries including those in Asia [ 23 26 ], Africa [ 27 , 28 ], South America [ 29 ] and the Middle-East [ 30 32 ]. These results highlight that challenges exist in both community [ 23 26 , 29 , 30 ] and hospital [ 27 , 28 , 31 ] provision of pharmaceutical care services. The major barriers to the delivery of comprehensive pharmacy services include the shortage of pharmacists, the lack of pharmaceutical care training programs and institutional obstacles.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous challenges and barriers faced by pharmacists in developing countries to implement and maintain sustainable pharmaceutical care services [ 23 , 27 , 30 ]. Most developing countries are struggling with a shortage of pharmacists [ 27 , 28 , 31 , 32 , 43 ], inadequate education and training for pharmacists [ 24 , 25 , 27 , 28 , 30 , 32 ], and support from other health care professionals [ 23 – 25 , 28 , 30 , 32 ]. Even though pharmacists from developing countries show great enthusiasm to promote and to devote themselves to the provision of pharmaceutical care services in their countries [ 27 ], efforts made to institutionalize pharmaceutical care services is minimal in many developing countries [ 27 , 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, government recognition and supervision of hospital pharmacists’ clinical services have been cited as a main driving factor, and participants perceived these services should not have been confined to few settings and national endorsement of these services have been found to be necessary. Bilal et al [ 45 ] have also confirmed that Ethiopian graduate pharmacists are very much enthusiastic to promote clinical pharmacy service but the challenge is the minimal effort made at the level of institutions.…”
Section: Discussionmentioning
confidence: 98%